Pemanfaatan Media Digital Pop Up Book dalam Pembelajaran Sejarah Khlufaur Rasyidin di Kelas 6 SD - Sallsa Nurfarida; Dhea Amanda Putri; Azmi Hofifah; Ani Nur Aeni (Journal on Education, 2023)
The research entitled The Use of Pop Up Book Digital Media in Learning History of Khulfaur Rasyidin in Grade 6 SD. The purpose of this study was to analyze the use of digital pop up book media on the effectiveness of learning the history of the Rashidun Khulafaur history. This study used the Design and Development (D&D) method by developing the ADDIE development model. Based on expert reviews from media experts, material experts and students at SDN Sukamaju digital learning media pop up books have an average pressure that shows a value of 83% with an interpretation of "very good" on expert judgment and shows an average promotion of 87.2% with the interpretation of "very good". The results of the study showed that there was an effectiveness of pop up book media in supporting the history of the Khulafaur Rasyidin in grade 6 SD as much as 80% in expert assessment and as much as 82% in student assessment. The ease of accessing material in this learning media shows a very good percentage of 80% in expert judgment and 81.1% in student assessment. Thus, pop up book digital learning media is an excellent medium to support learning in grade 6 elementary schools.